Handling Guest Supplies in Rooms at the Housekeeping Department of the Swiss-Bellinn Hotel Medan - Sembiring, Sepri Prananta (Cattleya Darmaya Fortuna, 2023)
Guest supplies are small items provided free of charge by hotels for guests to use during their stay. This study aims to examine how guest supplies are utilized by guests, how these supplies are stored in the Housekeeping Department, and how the inventory of guest supplies is managed in guest rooms at Swiss-Belinn Hotel Medan. The research employed a qualitative descriptive method, involving direct observation and interviews with a total of 36 participants, including 5 housekeeping staff, 1 housekeeping manager, and 30 hotel guests. The findings reveal that the management and inventory of guest supplies are not yet being carried out optimally. Notably, there is no established inspection procedure for guest supplies placed in the rooms. The study suggests that the hotel should implement more thorough inspections of guest supplies prior to placement in guest rooms to ensure service quality and guest satisfaction.